Survey of ICT and Education in Africa : Niger Country Report - Tutu Agyeman, Osei (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. The Republic of Niger is mostly desert and it is the poorest country in the world. Subsistence agriculture is the principal economic activity of its people who are confronted with inclement seasonal weather changes that further impact negatively on harvest volumes. The country has an underdeveloped electric power and communications infrastructure that can hamper its drive towards the deployment of ICT in the education sector and the public at large. Another challenge is the scarce financial resources that render the provision of basic educational infrastructure nearly intractable to government not to mention the supply of computers to schools. It is worthy to note, however, that the Niger government has implemented structures and made plans that should enable accelerated development in the ICT sector if the necessary donor support is found.